CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF RECURRENT LIVER ECHINOCOCCOSIS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article studies the morphological characteristics of recurrent liver echinococcosis.To determine the morphological modifications of echinococcosis, we analyzed the results of instrumental research methods (ultrasound, CT) and studied the surgical material in 252 patients who were operated on in the Surgery Department No. 1 of the multidisciplinary clinic of Samara State Medical University. The analysis of possible causes of recurrent liver echinococcosis is given depending on the morphological modifications of echinococcal cysts and the results of surgical treatment are presented. It was revealed that with multiple echinococcal liver lesions, which were found in 167 (66.2%) patients, in some cases a combination of various modifications of echinococcosis was observed. An association was mainly found between such forms as echinococcus hominis and echinococcus veterinorum.